CMOS Non‐tailed differential pair. (11th November 2015) - Di Cataldo, Giuseppe; Grasso, Alfio Dario; Pennisi, Salvatore; Scotti, Giuseppe; Trifiletti, Alessandro
Summary: A continuous‐time complementary metal–oxide–semiconductor differential pair that does not require the traditional tail current source as a way to control the direct current and common‐mode current is presented. Compared with a p ‐channel long‐tailed pair, the proposed non‐tailed solution operates under a higher maximum input common‐mode voltage that includes ( VDD  +  VSS )/2 even under low supply voltages. Experimental measurements on a prototype fabricated in a 0.35‐µm technology (with metal– oxide– semiconductor thresholds greater than 0.6 V) confirm this behavior for supply voltages as low as 1.2 V, whereas the long‐tailed pair with the same technology offers the same capability only for supplies higher than 1.6 V. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A continuous‐time complementary metal–oxide–semiconductor differential pair that does not require the traditional tail current source as a way to control the direct current and common‐mode current is presented. Compared with a p ‐channel long‐tailed pair, the proposed non‐tailed solution operates under a higher maximum input common‐mode voltage, that includes ( VDD  +  VSS )/2 even under low supply voltages. Experimental measurements on a prototype fabricated in a 0.35‐µm technology (with metal–oxide–semiconductor thresholds greater than 0.6 V) confirm this behavior for supply voltages as low as 1.2 V, whereas the long‐tailed pair with the same technology offers the same capability only for supplies higher than 1.6 V.